NUCLEAR MEDICINE: CURRENT ASPECTS IN STUDYING THE SUBJECT - Pocherniayeva, V.F.; Vasko, L.N.; Zhukova, T.A. (World of Medicine and Biology, 2018)
The article highlights some issues on the medical education and healthcare reformation that requires not only a big input of resources, but highly-trained and well-qualified medical professionals in various fields, including nuclear medicine. The training of specialists in nuclear medicine (NM) and radiologists consists in the providing targeted measures covering all directions of the radiology and NM in order to increase the professional level and to promote the enhancement of practical skills in the world of rapidly upgrading innovative technology. In accordance with the European requirements for training high-quality specialists and in order to enhance international cooperation in the area of education, the further implementation of the achievements of the innovations into the training includes a wide range of the latest technologies and methods, such as problem-oriented learning, interdisciplinary integrated training, simulation technologies, role-playing, games, technology of fundamental medical education, person-centered learning technology, rating system, technologies to evaluate learning quality, improvement of self-learning techniques, information technologies. At the same time, it is important to emphasize on the interdisciplinary integration between the subject, which is being taught, previous basic and subsequent related disciplines in accordance with the objectives of training medical specialists of various specialties and faculties. The implementation of this project will contribute to further improvement of the national regulatory framework in the field of higher medical education according to international and European legislation, to create appropriate conditions for training, retraining and advanced training of healthcare workers in higher education institutions and postgraduate education institutions in Ukraine. Thus, the effective solution of a number of issues referring healthcare requires a high-quality professional training for specialists in nuclear medicine; the implementation of appropriate organizational, methodological, psychological and pedagogical measures in all the directions of medical training of radiologists. The priority of the radiologists’ training includes the enhancement of qualification and professional skills, sophisticated incorporation of innovative teaching technologies into the education.
Keywords: nuclear medicine; training of specialists; integrated learning; higher medical education